2002
DOI: 10.1046/j.0003-2409.2001.02399.x
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin: pharmacology and its use in pain management

Abstract: SummaryAlthough its exact mode of action is not known, gabapentin appears to have a unique effect on voltage-dependent calcium ion channels at the postsynaptic dorsal horns and may, therefore, interrupt the series of events that possibly leads to the experience of a neuropathic pain sensation. Gabapentin is especially effective at relieving allodynia and hyperalgesia in animal models. It has been shown to be ef®cacious in numerous small clinical studies and case reports in a wide variety of pain syndromes. Gab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
300
1
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(316 citation statements)
references
References 110 publications
6
300
1
9
Order By: Relevance
“…Pregabalin has analgesic, anticonvulsant, and anxiolytic effects [5,6]. Several studies have demonstrated the efficacy of oral pregabalin on post-operative analgesia and reduction of parenteral analgesics [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Pregabalin has analgesic, anticonvulsant, and anxiolytic effects [5,6]. Several studies have demonstrated the efficacy of oral pregabalin on post-operative analgesia and reduction of parenteral analgesics [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…GBP is effective for neuropathic pain, diabetic neuropathy, postherpetic neuralgia and reflex sympathetic dystrophy (7). GBP has antihyperalgesic actions that selectively affect central sensitization (8). Over the past eight years, many trials have examined the efficacy of GBP for the treatment of early postsurgical pain.…”
mentioning
confidence: 99%
“…This is one reason why we chose to use pregabalin instead of gabapentin, which has a lower bioavailability at high doses and reaches peak plasma levels three times more slowly. 18 We therefore consider this dose sufficient to show a clinically relevant interaction, if it existed. Finally, the statistical method used in the present study is robust.…”
Section: Discussionmentioning
confidence: 99%